Commentary on “From unidimensional to multidimensional inequality: a review” - Karl Mosler (METRON, 2020)
These remarks supplement the paper of Andreoli and Zoli from a practical view-point, that is, of a data analyst who wishes to compare distributions of socio-economic endowments regarding their inequality.
Keywords: 510; Multidimensional inequality; Crossing Lorenz curves; Dominance tests